Activities of daily living and cognitive status: associations with urinary incontinence in Korea. Issue 3 (2nd July 2014) - Hong, Gwi‐Ryung Son; Park, Jeongok; Kang, Hye‐Kyung; Palmer, Mary H.
ABSTRACT Urinary incontinence (UI) is a prevalent condition among nursing home (NH) residents and a major cause of undesirable health outcomes and high costs of care. The overall aim is to determine the association between activities of daily living (ADL) and cognitive status among elderly residents with UI in NHs in Korea. Secondary analyses from a cross‐sectional study were performed in this study. Records of 221 elderly residents aged 65 or above who had no indwelling Foley catheter, were included. UI, ADL, cognitive status, depressive symptoms and co‐morbidities were measured through interviews with the residents and staff nurses. Logistic regression models were developed to assess the association between UI and ADL and cognitive status. The mean age of the participants was 80·3 (±7·2). Approximately 68% (n = 150) had UI based on information obtained from nurses. Age, gender, hypertension, arthritis, walking ability, ADL and cognitive status were significant factors in the univariate analyses. For the logistic regression model, ADL [odd ratio, 1·41; 95% confidence interval (CI), 1·26–1·57] and cognitive status (odd ratio, 1·10; 95% CI, 1·02–1·18) remained significant predictors for UI, after controlling for demographics and co‐morbidities. The ability to perform ADL and cognitive status are two factors that are strongly associated with UI. Future studies should examine the impact of environmental and organizational factors on UI in NH residents in Korea to develop a comprehensive and culturally sensitive intervention for this population.